Kinematic analysis and synthesis of the lever mechanism of crank press stamping - Tuleshov, A. K.; Merkibayeva, B.; Akhmetova, B. I. (Journal of Mathematics, Mechanics and Computer Science, 2020)
Expanding technical and technological capabilities of forging and stamping machines and equipment can be carried out by introducing new designs of actuators with wide functionality. These features are provided by the crank lever mechanisms of the press. This article presents a kinematic analysis and synthesis of a six-lever mechanism for stamping a crank press with a forging feed mechanism. We propose an analytical method for kinematic analysis of the mechanism, which allowed us to implement a numerical calculation program in the integrated Maple environment. Methods of kinematic synthesis of the six-lever crank press mechanism based on the standardsquare approximation, as well as the synthesis of the four-lever crank-slide forging feed mechanism have been developed. All the required constant geometric parameters of the stamping mechanism are determined; as a result, the mechanism implements the specified law of motion of the working slider with high accuracy. The comparative analysis was carried out in the ASIAN-2014 environment.